Oxygen vacancy enhancing mechanism of nitrogen reduction reaction property in Ru/TiO2 - Cheng, Shan; Gao, Yi-Jing; Yan, Yi-Long; Gao, Xu; Zhang, Shao-Hua; Zhuang, Gui-Lin; Deng, Sheng-Wei; Wei, Zhong-Zhe; Zhong, Xing; Wang, Jian-Guo (Journal of energy chemistry, 2019)
To search the new effective nitrogen reduction reaction (NRR) electrocatalyst is very important for the ammonia-based industry. Herein, we reported the design of a novel NRR electrocatalyst with Ru NPs loaded on oxygen-vacancy TiO2 (Ru/TiO2-Vo). Structural characterizations revealed that oxygen vacancy was loaded in the matrix of Ru/TiO2-Vo. Electrocatalytic results indicated that Ru/TiO2-Vo showed good NRR performance (2.11 µg h−1 cm−2). Contrast tests showed that NRR property of Ru/TiO2-Vo was much better than those of Ru/TiO2(B) (0.53 µg h−1 cm−2) and Ru/P25 (0.42 µg h−1 cm−2). Furthermore, density functional theory calculation results indicated catalytic mechanism of NRR and rate-determining step (*N2 + 1/2H2 → *N+*NH) was the potential-determining step with the overpotential requirement of 0.21 V. A combination of electronic structure analysis and catalytic measurement shed light on the synergistic effect of Ru and oxygen vacancy on the NRR performance. The Ru/TiO2-Vo electrocatalyst exhibited good NRR performance with a low voltage of −0.15 V to drive 2.11 µg h−1 cm−2 ammonia yield and DFT calculation revealed the important role of oxygen vacancy in the process. [Display omitted]